1984
DOI: 10.1177/073346488400300107
|View full text |Cite
|
Sign up to set email alerts
|

Youth's Attitudes Toward the Elderly

Abstract: This paper examines the attitudes of 35 male and 122 female college students toward six target groups of elderly individuals: males and females aged 65-74, 75-99 and 100 or older. A twenty-item semantic differential scale was used. Findings support the conclusion that the elderly are perceived as a heterogeneous group with age being an important discriminator, and with gender being less potent but, nevertheless, important. Older target groups were perceived less favorably than younger target groups, but actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 25 publications
1
27
1
1
Order By: Relevance
“…Scholars address an important issue surrounding how they and other adults believe youth view older adults and how children actually view older adults. Sanders, Montgomery, Pittman, and Balkwell, (1984) and Newman et al (1997) indicate that there is a gap between adults' perceptions of youth views and actual youth views of older adults. Through their study, Newman et al (1997) provided scholars information on children's views of older adults ''through the child's own values'' (p. 417).…”
Section: Individual Views Of Agingmentioning
confidence: 94%
“…Scholars address an important issue surrounding how they and other adults believe youth view older adults and how children actually view older adults. Sanders, Montgomery, Pittman, and Balkwell, (1984) and Newman et al (1997) indicate that there is a gap between adults' perceptions of youth views and actual youth views of older adults. Through their study, Newman et al (1997) provided scholars information on children's views of older adults ''through the child's own values'' (p. 417).…”
Section: Individual Views Of Agingmentioning
confidence: 94%
“…A number of investigations of attitudes toward older people (see Meshel, 1997, for a complete review) have found that individuals of different ages hold mixed to negative attitudes toward older people and the aging process (e.g., Caspi, 1984;Hummert, 1990;Sanders, Montgomery, Pittman, & Balkwell, 1984;Seefeldt, 1987;Tuckman & Lorge, 1953). Seminal research examining younger persons' attitudes toward older people was conducted by Hickey, Hickey, and Kalish (1968) who asked third grade students from socioeconomically diverse schools to write a short paper describing an ''old person like your grandparents.''…”
Section: Intergenerational Contact Attitudes and Stereotypes Of Adomentioning
confidence: 98%
“…Despite these phenomenal demographic changes and projections, studies of U.S. professionals and college students reveal that there is general apathy about working with older adults (Butler, 1990;Coren, Andreassi, Blood, & Kent, 1987;Shmotkin, Eyal, & Lomranz, 1992;Tan, Hawkins, & Ryan, in press). Studies indicate that overall attitudes toward older adults were in the positive or neutral range, but that they were negative regarding certain specific characteristics (Hawkins, 1996;Reed, Beall, & Baumhover, 1992;Sanders et al, 1984;Tan et al, in press). A study of U.S. baccalaureate social work majors found that while their overall attitudes toward young-old women were positive, their overall attitudes toward other groups of older adults were in the neutral range.…”
Section: Introductionmentioning
confidence: 91%
“…Overall attitudinal scores ranged from 20 (for most positive) to 140 (for most negative) with scores between 70 (3.5 x 20) and 90 (4.5 x 20) being considered neutral. Sanders et al ( 1984) established the validity of the instrument. Cronbach's Alpha coefficient of .83 indicates a high degree of internal consistency for the overall scale.…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation